2014
DOI: 10.1155/2014/313570
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids and Depression: Scientific Evidence and Biological Mechanisms

Abstract: The changing of omega-6/omega-3 polyunsaturated fatty acids (PUFA) in the food supply of Western societies occurred over the last 150 years is thought to promote the pathogenesis of many inflammatory-related diseases, including depressive disorders. Several epidemiological studies reported a significant inverse correlation between intake of oily fish and depression or bipolar disorders. Studies conducted specifically on the association between omega-3 intake and depression reported contrasting results, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
200
2
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(219 citation statements)
references
References 157 publications
(153 reference statements)
3
200
2
14
Order By: Relevance
“…Similar to the above cross-sectional data, prospective studies on the relationship between fatty acids and depression show substantial heterogeneity (Lucas et al 2011;Grosso et al 2014;Matsuoka et al 2017). Although other fatty acid classes have also been prospectively studied, most studies again focused on omega-3 fatty acid concentrations or intake.…”
Section: Longitudinal Observational Studiesmentioning
confidence: 78%
See 3 more Smart Citations
“…Similar to the above cross-sectional data, prospective studies on the relationship between fatty acids and depression show substantial heterogeneity (Lucas et al 2011;Grosso et al 2014;Matsuoka et al 2017). Although other fatty acid classes have also been prospectively studied, most studies again focused on omega-3 fatty acid concentrations or intake.…”
Section: Longitudinal Observational Studiesmentioning
confidence: 78%
“…Over the past 100-150 years, the ratio of omega-6 to omega-3 fatty acids in our modern Western diets has shown a steep increase from~1-2:1 to~20-30:1. Although alternative explanations have also been suggested (Dehue 2008;Bracke et al 2016), this may have contributed to a suggested parallel rise in burden of disease due to psychiatric disorders (Simopoulos 1999;Muskiet 2010;Hidaka 2012;Grosso et al 2014;van Elst et al 2014). Similar observations in more recently modernizing countries could suggest that history repeats itself (Sun and Ryder 2016).…”
Section: Historical Epidemiological Perspectivementioning
confidence: 97%
See 2 more Smart Citations
“…These effects are often evidenced by improvements in disease biomarker profiles or in health-related outcomes. As a result, they may play an important role to protect against cardiovascular morbidity and mortality, and might be beneficial in rheumatoid arthritis, diabetes, inflammatory diseases, childhood learning and behaviour, cancer prevention, and adult psychiatric and neurodegenerative illnesses [7,[19][20][21][22][23][24]. It has been shown recently that Omega-3 can protect myocardial infarction (MI) from ischemia/reperfusion injury in an isolated rat heart model [25] and promote early metabolic recovery after coronary artery bypass grafting (CABG) surgery [26].…”
mentioning
confidence: 99%